Evaluating sodium-ion pouch cell battery for renewable energy storage under extreme conditions - Shelke, Mehul; Boyer, Jamee M.; Mirzapure, Vinay; Pol, Vilas G. (Communications Chemistry, 2025)
A sodium-ion battery (SIB) is a sustainable energy storage technology based on abundantly available raw materials. It is a commercially viable option because of the processing similarity with Li-ion battery. Most of the energy storage studies focus on the near room temperature performance of different battery chemistries. Herein, we report the ultralow temperature performance of the SIB pouch cell. The cells fabricated using low-temperature compatible components showed significant specific energy values around 96, 74, and 46 Wh kg-1 at room temperature, -25 degrees C, and -50 degrees C, respectively. We demonstrated the battery performance under laboratory conditions as well as under actual windy and snowy environments. Such an exhibition highlights the use case of the SIB pouch cell as an emergency energy storage device in extreme weather conditions. Moreover, charging of SIB cell at -100 degrees C using polycrystalline Si solar cell is also reported, indicating the possibility of deployment for space expeditions.

Exploring FeSe2 and porous carbon composite as a cost-effective host for Al3+ in aqueous Aluminum ion batteries - Mirzapure, Vinay; Patrike, Apurva; Shelke, V, Manjusha (Electrochimica Acta, 2025)
Aluminum is a high-energy-density material with low cost, making rechargeable aluminum ion batteries (AIBs) a attractive alternative to alkali metal ion batteries. However, the practical development of aqueous AIBs is hindered by limited electrode. Herein, we report FeSe2-decorated porous nitrogen and sulfur-doped carbon spheres (FSPNSCS) as a cathode material for aqueous AIBs, with an emphasis on the reaction kinetics and electrochemical performance. FSPNSCS is synthesized through a hydrothermal approach, confirmed by comprehensive characterizations using X-ray Diffraction for crystalline structure validation and Scanning Electron Microscopy for analyzing composite morphology. Electrochemical properties and kinetics are probed using cyclic voltammetry and galvanostatic charge-discharge tests. Ex-situ XRD reveals a notable peak shift towards higher 2 theta values during discharge, indicating lattice contraction due to Al3+ insertion. Sulfur and nitrogen doping impart elasticity to the lattice structure, enhancing stability during cycling. Ex-situ XPS confirms Al3+ storage and minimal oxide formation, as further supported by microscopic elemental mapping with HRTEM. The FSPNSCS cathode achieves a reversible capacity of 60 mAh g- 1 at a current density of 200 mA g- 1. The system exhibits outstanding cycling stability, retaining over 90 % of its capacity at 500 mA g- 1 over 1000 cycles, highlighting its potential to advance aqueous AIBs for sustainable energy storage.
Keywords: Aqueous aluminum ion battery; cathode material; Electrochemistry; Transition metal selenide

Insights into electrolyte-solvent interactions and SEI formation for sustainable sodium-ion battery operation at low temperatures - Kim, Soohwan; Mirzapure, Vinay; Atwi, Rasha; Koppisetti, Heramba V. S. R. M.; Wasnik, Kundan; Rajput, Nav Nidhi; Shelke, Manjusha; Pol, Vilas G. (Small Methods, 2025)
Sodium-ion batteries (SIBs) show promise as an alternative to lithium-ion batteries. However, they face performance challenges at ultra-low temperatures (<-40 degrees C) due to slow Na+ transfer kinetics with conventional electrolytes. This limitation restricts their use in extreme environments such as polar regions and outer space. The presented systematic study addresses this challenge by modulating and tailoring the electrolyte composition for SIBs, enabling ultra-low temperature operation down to -110 degrees C for the first time. The comprehensive molecular dynamic and density functional theory calculations combined with experimental Raman spectroscopy and nuclear magnetic resonance studies of advanced electrolytes provided a deeper mechanistic understanding of the solvation structures and their impact on electrochemical performance. By varying the solvent composition with a combination of tetrahydrofuran and 2-Methyltetrahydrofuran solvents and sodium hexafluorophosphate (NaPF6) salt, the freezing point, solubility, and Na+ solvation structure of the electrolyte is modulated and studied in detail. The extensive anion engagement in the optimized mix solvent electrolyte facilitated the formation of a stable and inorganic-rich solid electrolyte interphase layer, ensuring low overpotentials and uniform Na+ deposition, yielding superior cycling stability. As a result, the developed electrolyte enables SIBs to achieve reversible capacities of 88 mAh g(-1) at -60 degrees C and 50 mAh g(-1) at -100 degrees C. These insights may contribute to developing improved energy storage devices suitable for challenging environmental conditions.
Keywords: contact-ion pair; solid electrolyte interphase (SEI); solvation; ultra-low temperature; XPS-depth Profiling

Investigations into the nucleation dynamics of the stable Na-metal anode: revealing the role of a tin-infused carbon nanofiber interlayer - Wasnik, Kundan; Yadav, Poonam; Ahuja, Manuj; Mirzapure, Vinay; Johari, Priya; Shelke, Manjusha V. (ACS Applied Materials & Interfaces, 2025)
Fundamental understanding and controlling of sodium nucleation are essential for enhancing the performance, safety, and longevity of sodium metal batteries, which is not yet clearly understood in the case of sodium metal batteries. The present study showcases how a modification in the host material influences nucleation kinetics. Current-time transient studies on copper, carbon nanofiber, and tin-embedded carbon nanofiber interlayers employing the Scharifker-Hills model elucidate the mode of nucleation. This work tries to delve deep and presents a case study on how a tin-based interlayer can not only minimize the barrier for sodium nucleation but also direct the sequential progressive and instantaneous nucleation of sodium metal while reducing the overpotential substantially, resulting in crystalline, uniform Na-metal deposition. Further, to account for the complex dynamics of solid electrolyte interphase (SEI) formation distinctly associated with alkali metal deposition, the SEI-fracture model has been included, and the quantification of electrochemical nucleation parameters is obtained. The results provide important insights into the sodium nucleation mechanism, paving the way to counter dendrite formation and SEI dissolution issues of the Na-metal anode.
Keywords: overpotential; progressiveand instantaneous nucleation; Scharifker-Hills model; SEI-fracture model; tin interlayer